TAWURAN REMAJA DAN SOLUSINYA DALAM PERSPEKTIF AL-QUR’AN - Hidayati, Hidayati (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2022)
One of the teenage problems that in Indonesia is brawls. This phenomenon has been the center of public attention from the past until now, as evidenced by the fact that teenagers are often seen walking in groups while destroying public facilities or attacking other teenagers. This study aims to find out the things that trigger brawls and the solutions contained in the Qur'an. The solutions in dealing with juvenile brawls seen from the perspective of the Qur'an are: first, teenagers must increase brotherhood and affection with each other. Second, if there are disputes and conflicts, teenagers must argue against the contradictory things in a good way, not with violence such as brawls. Third, reconcile and improve relations between warring brothers. Fourth, solving problems by way of deliberation, fifth, being a forgiving person, and calling on each other to do good. If the word sorry cannot solve the problem, then the next solution is to stay away from people who are ignorant/contrary to the truth. This research is a library research with descriptive-analytic aproach, using the maudu'i (thematic) interpretation method.